Rapid Response Team Activations in Pediatric Surgical Patients - Acker, Shannon N.; Wathen, Beth; Roosevelt, Genie E.; Hill, Lauren R. S.; Schubert, Anna; Reese, Jenny; Bensard, Denis D.; Kulungowski, Ann M. (European Journal of Pediatric Surgery, 2017)
Introduction The rapid response team (RRT) is a multidisciplinary team who evaluates hospitalized patients for concerns of nonemergent clinical deterioration. RRT evaluations are mandatory for children whose Pediatric Early Warning System (PEWS) score (assessment of child's behavior, cardiovascular and respiratory status) is ≥4. We aimed to determine if there were differences in characteristics of RRT calls between children who were admitted primarily to either medical or surgical services. We hypothesized that RRT activations would be called for less severely ill children with lower PEWS score on surgical services compared with children admitted to a medical service.Materials and Methods We performed a retrospective review of all children with RRT activations between January 2008 and April 2015 at a tertiary care pediatric hospital. We evaluated the characteristics of RRT calls and made comparisons between RRT calls made for children admitted primarily to medical or surgical services.Results A total of 2,991 RRT activations were called, and 324 (11%) involved surgical patients. Surgical patients were older than medical patients (median: 7 vs. 4 years; p < 0.001). RRT evaluations were called for lower PEWS score in surgical patients compared with medical (median: 3 vs. 4, p < 0.001). Surgical patients were more likely to remain on the inpatient ward following the RRT (51 vs. 39%, p < 0.001) and were less likely to require an advanced airway than medical patients (0.9 vs. 2.1%; p = 0.412). RRT evaluations did not differ between day and night shifts (52% day vs. 48% night; p = 0.17). All surgical patients and all but one medical patient survived the event; surgical patients were more likely to survive to hospital discharge (97 vs. 91%, p < 0.001)Conclusions RRT activations are rare events among pediatric surgical patients. When compared with medical patients, RRT evaluation is requested for surgical patients with a lower PEWS score and these children are less likely to require transfer to a higher level of care, suggesting that pediatric surgery team, families, and nursing staff may not be as comfortable with clinical deterioration.
Keywords: rapid response team; code team; PEWS score